Qualidade de vida dos agentes comunitários de saúde da estratégia saúde da família do município de Vitória-ES - Landeiro, Graziela Macedo Bastos (2009)
Community health agents (CHA) are often subjected to physical and psychological demands which may jeopardize both their own well-being and the quality of care they provide as health workers. This study aims at identifying the socio-demographic factors associated with their personal well-being and job satisfaction in the work they develop under the guidelines for family health care, as established by the municipality of Vitoria. A qualitative, analytical, descriptive and cross-sectional research design was adopted and 241 CHAs participated as subjects. A semistructured questionnaire, based on the one set up by the Instituto Brasileiro de Geografia, and the WHOQOL-Bref questionnaire were both used to assess quality of life. Participants were found to be predominantly female in the 30-39 age group; most were married, non-Caucasian, with high school level of schooling and professed religious belief. Quality of life was rated well by the subjects, with maximum scores for physical and social relations domains, while the environment domain scored the lowest. This domain encompassed physical environment (pollution noise, traffic, and climate), financial resources (wages) and opportunities for further education, training and recreation. Lower quality of life was significantly associated, in all domains, with the neighborhood where the subjects worked, with highest risk for divorcés with lower scores in social relations working at health units in the center of Vitoria. Results were similar for the environment domain amongst non-Caucasian and widowers working at health units in the neighborhood of São Pedro Given the importance of the work undertaken by CHAs and its impact in the community as a whole, it is critical to further debates and develop new strategies to ensure both their well-being and job satisfaction as they will positively affect the quality of health services provided for the population.